2017
DOI: 10.1016/j.annemergmed.2016.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Etomidate and Ketamine for Induction During Rapid Sequence Intubation of Adult Trauma Patients

Abstract: Study objective Induction doses of etomidate during rapid sequence intubation (RSI) cause transient adrenal dysfunction, but its clinical significance on trauma patients is uncertain. Ketamine has emerged as an alternative for RSI induction. Among adult trauma patients emergently intubated, we compared clinical outcomes among those induced with etomidate and ketamine. Methods The study entailed a retrospective evaluation of a four-year (January 2011–December 2014) period spanning an institutional protocol sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 42 publications
2
50
0
2
Order By: Relevance
“…We have previously validated these data-collection techniques for relevant data points. 15,22,23 Coexisting conditions at baseline were summarized with the Elixhauser Comorbidity Index score. 24 …”
Section: Methodsmentioning
confidence: 99%
“…We have previously validated these data-collection techniques for relevant data points. 15,22,23 Coexisting conditions at baseline were summarized with the Elixhauser Comorbidity Index score. 24 …”
Section: Methodsmentioning
confidence: 99%
“… Ketamine has a preferable cardiorespiratory safety profile . Ketamine has been considered contraindicated in patients with head trauma due to the concern of increasing intracranial pressure, but the current evidence to refute ketamine use is not strong . Reports have suggested that ketamine does not reduce regional glucose metabolism or augment oxygen consumption but could benefit patients with an intracranial injury by a catecholamine‐mediated increase in cerebral perfusion.…”
Section: Special Circumstance: Patients With Traumamentioning
confidence: 99%
“… 39 Interventions can be assessed and judged for usefulness, deployment, and retention within the armamentarium of initial trauma care. Rapid sequence intubation continues to be refined 40 and anatomic positioning for needle decompression has been altered. 41 The utility, timing, and usefulness of diagnostic peritoneal lavage, CT, ultrasound, pericardiocentesis, emergency thoracotomy, and balloon occlusion of the aorta continue to be evaluated.…”
Section: Procedural Interventionsmentioning
confidence: 99%